Analisis Pengaruh Kualitas Pelayanan Dan Disiplin Kerja Karyawan Terhadap Kepuasan Pasien Askes Di Pt Askes Kediri - Yogi Yunanto (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2016)
Abstract This research is motivated researcher observations and experiences, especiallythat of PT Askes Kediri Askes Patients who are less sensitive in terms of quality ofservice and low sense of employee discipline in obeying the rules. As a result, manypatients who are less conscious and lazy to perform administrative activities.The problem of this study is (1) Is the quality of health care insurance in effecton patients’ satisfaction, PT Askes Kediri? (2) Is the employee disciplinary effect onpatient satisfaction in PT Askes Kediri? (3) Is the quality of service and employeediscipline effect on patient satisfaction in PT Askes Kediri?This study used a qualitative approach to formulating a hypothesis, then thehypothesis will be tested using a quantitative approach. Where the data obtained willbe calculated using the formula and test the statistical analisisaConclusion The results of this study were (1) Variable quality of service  (X1)to simultaneously deliver significant influence on patient satisfaction in PT Askeskediri with a probability value of b1 is 0.017 less than 0.05. (2) Variable disciplineemployees (X2) simultaneously providing significant influence on patient satisfactionin PT Askes Kediri with a probability value of b2 is 0.031 less than0.05. (3) Variable quality of service (X1) has a regression coefficient (β) for = 0.149,employee discipline (X2) is 0.123, thus it can be said that the service quality variable(X1) has a dominant influence on patient satisfaction in PT Askes Kediri .Conclusionsbased on these results, it is recommended: (1) the principal purpose of the applicationquality of service and employee discipline is to give satisfaction to the patient.Therefore, employees should always put quality of service and employee discipline.(2) the employee must be continuously examined, to prove whether the quality ofcare and discipline works are in accordance with the applicable rules. Keywords: Quality of Service, Employee Discipline, Patient Satisfaction.